Financial Control and Management of Police Services - A Case Study of Punjab State - Sidhu, H. S.; Bains, S. S. (Indian Journal of Finance, 2008)
Money is the bloodstream of administration and it is required for running all the activities of Government. Each officer who has some responsibility for conducting Government activities has to exercise financial control. In departments like the police, where receipts are negligible, control over expenditure is important and financial control largely means control over expenditure. Police department bears the responsibility for maintenance of peace, which is a pre-condition for sustained economic development. Internal disturbances and high crime rates prove detrimental to the economic health of a nation. In the present times, the nations facing such problems are incurring huge public expenditure on maintaining defence and internal security. The present study is an attempt to have an overview of the main components of financial administration of police department and to analyze the financial issues before the police services in Punjab. Further an attempt has been made to examine the variations in the nature and quantum of total police expenditure in Punjab during different phases of crime from 1984 to 2004. Total police expenditure at constant prices in Punjab (which is considered amongst the group of states maintaining very high police expenditure) has increased by 4.9 times during the period of twenty years (1984-2004) at an average annual C.G.R. of 8.50%. The C.G.R. of terrorism period (1984-1994) was high to the extent of 16.49% as compared to C.G.R. of post terrorism period (1994-2004) which was estimated as 5.55%.